Analisis Kritis Kesalahan Kognitif Mahasiswa Semester II Jurusan Matematika UNIMED dalam Pemecahan Masalah Geometri Berbasis Etnomatematika melalui Representasi Rumah Adat Indonesia - Hiyoshi Friyona Silalahi; Adam Rafli; Iren Kurnia Nadapdap; Sergi Br Sembiring; KMA Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the cognitive errors of second-semester students in solving geometry problems based on ethnomathematics through the representation of Indonesian traditional houses. This research employed a descriptive qualitative approach involving 20 students as respondents. Data were collected through a questionnaire consisting of five descriptive geometry problems designed within an ethnomathematics context and documented via Google Drive. The data, in the form of students’ written responses, were analyzed by identifying errors in each problem. The results indicate that students made errors in identifying geometric shapes, understanding and interpreting problem statements, reading information accurately, performing rounding procedures, and distinguishing between plane and solid figures. From all respondents, five students were selected for in-depth analysis based on the variation of errors. The findings show that these errors are not only procedural but also related to conceptual understanding and visual interpretation. Therefore, more contextual learning with an emphasis on conceptual understanding is needed to minimize students’ cognitive errors.